Enhancing organization demand for innovation through entrepreneurial leadership and social networks - Mokhber, Mozhdeh (2015)
This study aims to investigate the direct and indirect effect of entrepreneurial leadership on organization demand for innovation. Over the past years academic debates have mostly focused on individual’s demand for innovation while emphasizing on the organization's success in producing new products and services to individual customers. However the organizational customers and organization's demand to use innovation in day to day work has been generally neglected. Since previous studies identified leadership as an important determinant of innovation in the organization, this research proposes a conceptual framework to explore the effect of entrepreneurial leadership on organization’s demand for innovation. The success of entrepreneurial leadership depends not only on the behaviors of the leader, but also on the characteristics of their followers in demonstrating entrepreneurial behaviors. Therefore this study aims to examine the moderating role of follower’s reliance on social networks to recognize new opportunities on the relationship between entrepreneurial leadership and organization’s demand for innovation. A sample of Malaysia Top 100 Companies participates in this research and the hypotheses are evaluated using Partial Least Squares (PLS) analysis. This research makes an important contribution by providing empirical evidences that may support entrepreneurial leaders and their firms to identify and generate more opportunities and enact them in ways that increase the organization's receptivity towards innovation.